Membentuk Generasi Anti-Bullying di Desa Dempelrejo (Seminar Anti-Bullying di SDN Dempelrejo) - Fariza Mukholifah; M. Roikhan Ali Anwar; Ahmad Munif; Alya Afi Malika Putri; Arfika Nur Aini Dalila; Siti Afifah; Fia Muna Ayu Anjana; saifudin (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
The prevalence of bullying, even among elementary school children, requires serious attention from all parties. In an effort to shape a generation free from bullying behavior, the KKN MIT 18 program in Dempelrejo Village conducted an anti-bullying seminar at SDN 1 Dempelrejo. This program aimed to provide education on the types of bullying, its impact, and prevention strategies. The seminar was met with high enthusiasm from the students, and through the materials and interactive sessions, they are expected to understand and apply anti-bullying values in their daily lives. The results of the activity showed an increased understanding among students regarding the dangers of bullying and the importance of creating a safe and comfortable school environment.